Moderasi Beragama Perspektif Pluralisme Abdurahman Wahid (Gus Dur) - Nurhidayah Nurhidayah; Andika Putra; Dion Pratama Putra; Mursyidatul Fadhliah; Yassirly Amrona Rosyada (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to analyze religious moderation from the perspective of Abdurahman This study aims to analyze religious moderation from the perspective of Abdurahman Wahid's pluralism. This study uses a qualitative approach through descriptive-analytical methods. The result and discussion of this research is to try to find out the religious moderation of Gus Dur's pluralism perspective, because Gus Dur is dubbed as the father of national pluralism. This study concludes that religious moderation in Gus Dur's pluralism perspective is that religious moderation is a conception that can build tolerance and harmony in order to strengthen national unity and integrity. And it is recommended to further researchers to be able to further develop research like this to be even better so that it can complement the shortcomings that exist in this study.